Association of NS1 Antigen, IgM, IgG Antibodies and RT-PCR in the Diagnosis of Dengue Virus Infection - Naureen Saeed, Fatima-Tuz-Zuhra, Nadeem Ikram,Tanveer Akhtar (Journal of Rawalpindi Medical College, 2017)
Background: To determine the association of ELISA based serological markersNS1 antigen, IgM, IgG antibodies and RT-PCR in the diagnosis of dengue virus infection Methods: In this descriptive cross sectional study 420 serum samples from patients with suspicion of dengue fever were tested for detection of dengue by NS1 antigen ELISA, IgG, IgM ELISA. RT-PCR for dengue was carried out in all NS1 antigen ELISA positive cases for confirmation of dengue. Results: Out of 420 cases , 249 cases were positive for either one of the three markers NS1, IgM,IgG. Males constituted 71.66%.Two hundred and two (48.09%) were positive for NS1 only,13 (3.09%) were positive for NS1 and IgG, 07 (1.66%) were NS1, IgM and IgG positive,16 (3.80%) were positive for IgG only ,11 (2.61%) were positive for NS1 and IgM whereas 171 (40.17%) samples were reported negative for NS1, IgM and IgG.RT-PCR was conducted on 233 NS1 positive cases out of which 80.06% cases turned out positive. Maximum number of cases belonged to DEN-2 genotype. Conclusion: Early diagnosis helps in improved patient care, suitable treatment, prevents severe complications and helps limit the spread of the disease. RT PCR is a reliable test for the diagnosis of acute dengue fever.